2015
DOI: 10.1371/journal.pone.0144914
|View full text |Cite
|
Sign up to set email alerts
|

Application of Electron Paramagnetic Resonance (EPR) Oximetry to Monitor Oxygen in Wounds in Diabetic Models

Abstract: A lack of oxygen is classically described as a major cause of impaired wound healing in diabetic patients. Even if the role of oxygen in the wound healing process is well recognized, measurement of oxygen levels in a wound remains challenging. The purpose of the present study was to assess the value of electron paramagnetic resonance (EPR) oximetry to monitor pO2 in wounds during the healing process in diabetic mouse models. Kinetics of wound closure were carried out in streptozotocin (STZ)-treated and db/db m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 72 publications
5
16
0
3
Order By: Relevance
“…In contrast, alterations of ASC functions in diabetic rodent models were also described [6,1618]. Because Desmet et al demonstrated prolongation of hypoxia in diabetic mice in vivo [19], we postulated that hyperglycemia coupled with hypoxia may influence the function of ASC. Veriter et al also demonstrated preliminary results concerning the capacity of VEGF released during hypoxia and normoxia conditions and its function in in vitro glucose concentrations.…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, alterations of ASC functions in diabetic rodent models were also described [6,1618]. Because Desmet et al demonstrated prolongation of hypoxia in diabetic mice in vivo [19], we postulated that hyperglycemia coupled with hypoxia may influence the function of ASC. Veriter et al also demonstrated preliminary results concerning the capacity of VEGF released during hypoxia and normoxia conditions and its function in in vitro glucose concentrations.…”
Section: Introductionmentioning
confidence: 87%
“…Prolonged hypoxia, e.g. via microangiopathy, is considered to play a pathogenetic role in diabetic wounds . Moreover, HIF‐1 signalling was shown to be disrupted in diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…Electron paramagnetic resonance oximetry (EPR oximetry) allows for direct, repeated, noninvasive measurements of oxygen through injection of a paramagnetic source into tissue . Although it has been used primarily to measure tumor oxygenation in response to radiation and chemotherapy, interest in utilizing it to measure tissue oxygen in wound healing and surgical flaps is growing . Using transcutaneous oximetry (TcO 2 ) as a control, we demonstrate the accuracy and ease with which EPR oximetry may be used to monitor flap oxygenation and viability.…”
Section: Introductionmentioning
confidence: 99%